Answer: y = 1
==========================================================
Step-by-step explanation:
There are two ways to solve this
The first method will have us distribute the 2 through to each term, then we solve for y
6 = 2(y+2)
6 = 2y+4 .... distribute
2y+4 = 6
2y = 6-4 .... subtract 4 from both sides
2y = 2
y = 2/2 .... divide both sides by 2
y = 1 is the answer
-------------
Or we can solve through this set of steps
6 = 2(y+2)
6/2 = y+2 ...... divide both sides by 2
3 = y+2
y+2 = 3
y = 3-2 .... subtract 2 from both sides
y = 1
Either way, we get the same answer.
-------------
To check the answer, replace every copy of y with 1
Simplifying should lead to 6 on the right side
6 = 2(y+2)
6 = 2(1+2)
6 = 2(3)
6 = 6
Since we get the same thing on both sides, this means the last equation is true. This in turn means the first equation is true when y = 1. Therefore, the solution has been confirmed.